The research on business concentration in Lithuanian economy - Romualdas Ginevičius; Algirdas Krivka (Business: Theory and Practice, 2009)
The trend of growing business concentration has become common for the process of developing of Lithuanian economy nowadays; besides, high concentration in certain industries could be related to the former state monopoly privatization. A market or an industry, dominated by several producers or sellers, is considered to be oligopoly. The economists of the neo-classical school, accompanied by the scholars of modern microeconomics and industrial organization, associate oligopoly with a threat of cartels or other agreements on coordination of behaviour, improper use of the dominating position, consumer ineffective equilibrium even in case of fair competition. The article presents the complex research on business concentration in the main sectors of Lithuanian industry, trade and services in an attempt to identify oligopolistic industries and evaluate their weight in the economy of the state. The evaluation of concentration is quantitative: the calculations are made by applying the concentration and the Herfindahl-Hirschman ratios – the ones that are most commonly used in similar researches. The 4-digit (detailed) classification of economic activities, approved by the Department of Statistics to the Government of the Republic of Lithuania, is used to distinguish between industries. Published economic activity level statistics for the calendar year 2006 together with the data on the sales of the largest enterprises in potentially concentrated industries are involved in the research.